2007
DOI: 10.1111/j.1742-4658.2007.06040.x
|View full text |Cite
|
Sign up to set email alerts
|

Lending a helping hand, screening chemical libraries for compounds that enhance β‐hexosaminidase A activity in GM2 gangliosidosis cells

Abstract: Enzyme enhancement therapy is an emerging therapeutic approach that has the potential to treat many genetic diseases. Candidate diseases are those associated with a mutant protein that has difficulty folding and/or assembling into active oligomers in the endoplasmic reticulum. Many lysosomal storage diseases are candidates for enzyme enhancement therapy and have the additional advantage of requiring only 5–10% of normal enzyme levels to reduce and/or prevent substrate accumulation. Our long experience in worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 46 publications
1
41
0
2
Order By: Relevance
“…5). We then applied a more general test for potential PC-activity, the ability to attenuate the heat inactivation of the target enzyme [29], at pH 4.5 as compared to pH 7.0. Interestingly at 50 °C, Gcc has a half-life (T 1/2 ) of 3.3 min at pH 4.5, but at pH 7.0 it drops to only 1.7 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). We then applied a more general test for potential PC-activity, the ability to attenuate the heat inactivation of the target enzyme [29], at pH 4.5 as compared to pH 7.0. Interestingly at 50 °C, Gcc has a half-life (T 1/2 ) of 3.3 min at pH 4.5, but at pH 7.0 it drops to only 1.7 min.…”
Section: Resultsmentioning
confidence: 99%
“…Both approaches have been reported to target the ERQC in different ways, and if their proposed mechanisms of action are correct, they could act additively or even synergistically. The aim of EET is to increase the stability of the native conformation of the mutant enzyme in the ER, allowing more of it to be engaged by the ER transport machinery for transport to the lysosome [27,29]. To date successful chaperones have also been competitive inhibitors of their target enzymes, i.e., pharmacological chaperones (PCs).…”
mentioning
confidence: 99%
“…These screens have led to the discovery that pyrimethamine (PYR, 5-(4-chlorophenyl)-6-ethyl-2,4-pyrimidinediamine) is also a good candidate for a PC. 9 PYR is more widely recognized as an antimalarial drug that targets dihydrofolate reductase (DHFR). The structure of the DHFR:PYR complex revealed that the drug binds to the active site of DHFR and acts as a competitive inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…The second small molecule approach is enzyme enhancement therapy (EET) [7,8], which is still under investigation, but has shown some promising preclinical results in at least four enzyme deficiencies [3,9] with several Phase I and Phase II clinical trials being completed (e.g. [10]).…”
Section: Introductionmentioning
confidence: 99%
“…The attractiveness of this strategy resides in its applicability to a wide range of both inherited and acquired pathologic conditions associated with protein misfolding; e.g. Adult Tay-Sachs [7] and ischemic diseases [16], respectively. On the negative side, each target protein requires a different molecule and not all mutations, not even all missense mutations, will be responsive.…”
Section: Introductionmentioning
confidence: 99%